3x+7=8x-63

Simple and best practice solution for 3x+7=8x-63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+7=8x-63 equation:


Simplifying
3x + 7 = 8x + -63

Reorder the terms:
7 + 3x = 8x + -63

Reorder the terms:
7 + 3x = -63 + 8x

Solving
7 + 3x = -63 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
7 + 3x + -8x = -63 + 8x + -8x

Combine like terms: 3x + -8x = -5x
7 + -5x = -63 + 8x + -8x

Combine like terms: 8x + -8x = 0
7 + -5x = -63 + 0
7 + -5x = -63

Add '-7' to each side of the equation.
7 + -7 + -5x = -63 + -7

Combine like terms: 7 + -7 = 0
0 + -5x = -63 + -7
-5x = -63 + -7

Combine like terms: -63 + -7 = -70
-5x = -70

Divide each side by '-5'.
x = 14

Simplifying
x = 14

See similar equations:

| -12=-7–7/2s | | 14+7K=9K-2 | | -8(10x+3)=376 | | f(x)=4x^2-24x+31 | | 19v=-114 | | 3+4(x+6)=11 | | -9=2/3x–17 | | 8-4x=4-3(2x-6) | | 5(8v-8)=-6 | | 2x+3=-55 | | Y=1/2X-18 | | 65=5(5x-17) | | -2(x-3)=5(2x+13) | | 14+A=2-2A | | 2/3x–17=-9 | | -q=-52 | | f(x)=6xsquar | | (15)65=5(5x-17) | | 1-r=9 | | ln(x-3)=ln(1/x) | | 9xy-4+xy+8= | | 2x-5x+3-5=-17 | | 4x+8x+6x=x | | -10=3X+4-2 | | -310=5(7x-6) | | y+5.4=-8.5 | | v-52=8 | | Log19(18m/y) | | 5(-7x-12)=-480 | | 28=1/2•7•h | | w-16=1.4 | | 5=1-5 |

Equations solver categories